2013
DOI: 10.1149/2.109311jes
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Properties of Electrodeposited Nanocrystalline Ni-Fe Alloys

Abstract: Nickel-iron alloy coatings were produced by electrodeposition from an additive free electrolyte, at room temperature and current density in the range of 1 to 5 A dm–2, with Fe content up to 75 wt.%. The structure and mechanical properties of the electrodeposited alloys are reported in the present work and analysed focusing on structure-property relationships. In particular, the influence of the hydrogen evolution reaction is highlighted as a process factor affecting alloy phase structure, notably the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…49 The linear increase of tensile stress in fcc NiFe electrodeposited films was observed earlier. 23,50 Our results (Fig. 18) show the linear increase of tensile stress in both fcc and bcc NiFe alloys.…”
Section: Magnetic Properties Of Nife Nanowire Arrays With 8-55%fe-mentioning
confidence: 66%
“…49 The linear increase of tensile stress in fcc NiFe electrodeposited films was observed earlier. 23,50 Our results (Fig. 18) show the linear increase of tensile stress in both fcc and bcc NiFe alloys.…”
Section: Magnetic Properties Of Nife Nanowire Arrays With 8-55%fe-mentioning
confidence: 66%
“…To date, with respect to the formation of a metastable bcc phase in the electroplated Fe-Ni alloy in the Invar composition range, several mechanisms related to hydrogen generation and hydride formation during electroplating have been proposed; 46 however, we have yet to discover the details of such mechanisms. It has been reported that hydrogen generation and hydride formation during the Invar alloy electroplating generate high-density structural defects, which may induce a metastable bcc structure.…”
Section: Alloy Composition Deposition Rate Surface Morphology and Cry...mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] These properties are largely dependent upon the structure and morphology of the electrodeposit, which in the case of cobalt can vary dramatically with overpotential, electrolyte pH, and the presence of strongly adsorbing anions. 2,[12][13][14][15][16] …”
mentioning
confidence: 99%